Insecticidal effects of eudesmanes from Pluchea sagittalis (Asteraceae) on Spodoptera frugiperda and Ceratitis capitata - Sosa, A. (2017)
Eudesmanoids play an important role in the protection of plants against herbivores. Pluchea sagittalis (Lamarck) Cabrera (Asteraceae) is widespread in tropical South America and contains compounds that provide protection against phytophagous insects. In the present work we isolated seven sesquiterpenoids with eudesmane skeletons that were evaluated for their insecticidal activities against Spodoptera frugiperda and Ceratitis capitata, pests that cause serious damage to crops in the Argentine northwest. The Eudesmanes were incorporated at different concentrations to the diet of Spodoptera frugiperda. In the choice test, larval feeding behavior was altered. The eudesmanes 1, 5 and 7 showed the highest activity with feeding election indexes (FEI) of 50, 50, and 72 %, respectively at 200 µg/g of diet. When tested for insecticidal activity using neonate larvae with the nochoice artificial diet bioassays, eudesmane 1 was the most toxic in the larval stage (LD50 177.80 mg/g of diet). Compounds 5 lowered the percentage of adult emergence and produced the most malformations (72%) compared with control. Drastic effects were observed in the oviposition deterrence activity against C. capitata. The maximum oviposition deterrence (87 %) was recorded with eudesmane 5 at dose 30 µg/cm2 of artificial fruit. Finally, eudesmanes 6 and 7 showed significant larval and pupal mortality against the first generation larvae of viable eggs oviposited by females fed with the treated diet (100 µg / g artificial diet).